The Iliad of Homer - Homer; Lattimore, Richmond Alexander, 1906-1984.; Martin, Richard P. (Chicago : University of Chicago Press, 2011)
Presents Homer's classic epic of the Trojan War, which follows proud Greek soldier Achilles from his angry dispute with his king, Agamemnon , to his battle with and brutal treatment of Troy's great hero, Hector; and includes a glossary of names and an introduction.
Includes bibliographical references.
Keywords: Homer